Von Willebrand factor and alkaline phosphatase predict re-transplantation-free survival after the first liver transplantation. Issue 1 (February 2017) - Wannhoff, Andreas; Rauber, Conrad; Friedrich, Kilian; Rupp, Christian; Stremmel, Wolfgang; Weiss, Karl Heinz; Schemmer, Peter; Gotthardt, Daniel N
Background: After liver transplantation (LT), there are liver-related, infectious and cardiovascular complications that contribute to reduced graft survival. These conditions are associated with an increase in the Von Willebrand factor antigen (VWF-Ag), which was previously correlated with survival in cirrhotic patients. Objective: Evaluate VWF-Ag as a predictive marker of re-transplantation-free survival in patients after LT. Methods: We measured VWF-Ag in patients after first LT and then followed them prospectively with regard to the primary endpoint, namely re-transplantation-free survival. Results: There were 6 out of 80 patients who died or received re-LT during follow-up. In these patients, the median VWF-Ag was 510.6%, which was significantly higher ( p = 0.001) than in the patients who were alive at the end of follow-up (with a median VWF-Ag = 186.8%). At a cut-off of 286.8%, VWF-Ag was significantly correlated with re-transplantation-free survival ( p < 0.001). VWF-Ag was independently associated with re-transplantation-free survival in a multivariate analysis; as was alkaline phosphatase (ALP), but not the model of end-stage liver disease (MELD) score, donor age, nor cold ischemia time. A score combining VWF-Ag and ALP showed an impressive capability in the receiver operating characteristic (ROC) analysis (with area under the curve (AUC) = 0.958) to distinguish between patients with regard to the primary endpoint. Conclusions: VWF-Ag is a non-invasive marker that can predict outcome in patients after LT. Its diagnostic performance increased when combined with ALP in a newly developed scoring system.